Innovative Approach to Producing Palladium-103 for Auger-Emitting Radionuclide Therapy: A Proof-of-Concept Study - Aicha Nour Laouameria; Mátyás Hunyadi; Attila Csík; Zoltán Szűcs (MDPI AG, 2024)
Auger-emitting radionuclides, exemplified by Pd-103, exhibit considerable therapeutic potential in cancer treatment due to their high cytotoxicity and localized biological impact. Despite these advantages, the separation of such radionuclides presents a complicated challenge, requiring intricate and time-intensive "wet chemistry" methods attributed to the exceptional chemical inertness of the associated metals. This study proposes an innovative solution to this separation challenge through the design and implementation of a piece of radionuclide separation equipment (RSE). The equipment employs a dry distillation approach, capitalizing on differences in partial vapor pressures between irradiated and resulting radioactive metals, with a diffusion-driven extraction method applied to separate Pd-103 radionuclides generated via the proton irradiation of Rh-103 at cyclotron. Our optimization endeavors focused on determining the optimal temperature for effective metal separation and adjusting the diffusion, evaporation, and deposition rates, as well as addressing chemical impurities. The calculations indicate 17% ± 2% separation efficiency with our RSE. Approximately 77 ± 2% and 49 ± 2% of the deposited Pd-103 were isolated on substrates of Nb foil and ZnO-covered W disc, respectively. The proposed innovative dry distillation method that has been experimentally tested offers a promising alternative to conventional separation techniques, enabling enhanced purity and cost-efficient cancer treatment strategies.